An approach to difficult airway in infants: Comparison of GlideScope® Spectrum LoPro, GlideScope® Spectrum Miller and conventional Macintosh and Miller blades in a simulated Pierre Robin sequence performed by 90 anesthesiologists - Irouschek, Andrea; Moritz, Andreas; Kremer, Sven; Fuchte, Tobias; Danzl, Anja; Schmidt, Joachim; Golditz, Tobias (PLoS ONE, 2023)
BACKGROUND: Airway management can be challenging in neonates and infants. The Pierre Robin sequence (PRS) is a condition characterized by micrognathia, glossoptosis and airway obstruction. The airway management of these patients poses great challenges for anesthesiologists and pediatricians alike. To date, there has been no direct comparison of the hyperangulated GlideScope® Spectrum LoPro (GLP), the straight GlideScope® Spectrum Miller (GSM), a conventional Macintosh (MC) and a conventional Miller blade (ML) in patients with PRS. METHODS: For this purpose, 90 anesthesiologists (43 with limited experience, 47 with extensive experience) performed orotracheal intubation on an Air-Sim® Pierre Robin X manikin using GLP, GSM, MC and ML in randomized order. 'Time-to-vocal-cords', 'time-to-intubate', 'time-to-ventilate', the severity of oral-soft-tissue-trauma and the subjective evaluation of each device were recorded. RESULTS: A significantly faster and better view of the vocal cords and lower oral-soft-tissue-trauma was achieved using the GLP (p<0.001). Though, there were no significant differences in the 'time-to-intubate' or 'time-to-ventilate'. The highest intubation success rate was found with GSM and the lowest with GLP (GSM 100%, ML 97.8%, MC 96.7%, GLP 93.3%). When using the videolaryngoscopes, there were no undetected esophageal intubations but in six cases prolonged attempts of intubation (>120s) with the GLP. In the sub-group with extensive experience, we found significantly shorter intubation times for the GSM and ML. The GLP was the tool of choice for most participants, while the conventional MC received the lowest rating. CONCLUSIONS: Videolaryngoscopy leads to increased safety for the prevention of undetected esophageal intubation in the airway management in a PRS manikin. Hyperangulated blades may ensure a good and fast view of the vocal cords and low oral-soft-tissue-trauma but pose a challenge during the placement of the tube. Specific skills and handling seem to be necessary to ensure a safe tube placement with this sort of blades.
CRIS-Team Scopus Importer:2023-08-11

Combined recurrent laryngeal nerve monitoring and one-lung ventilation using the EZ-Blocker and an electromyographic endotracheal tube - Moritz, Andreas; Schmidt, Joachim; Schreiner, Waldemar; Birkholz, Torsten; Sirbu, Horia; Irouschek, Andrea (Journal of Cardiothoracic Surgery, 2019)
Background: Intraoperative neuromuscular monitoring (IONM) is a widespread procedure to identify and protect the recurrent laryngeal nerve (RLN) during thyroid surgery. However, for left thoracic surgery with high risk of RLN injury, both reliable recurrent laryngeal nerve monitoring and one-lung ventilation could interfere. Methods: In this prospective study, a new method for IONM during one-lung ventilation combining RLN monitoring with an electromyographic (EMG) endotracheal tube (ETT) and lung separation using the EZ-Blocker (EZB) is described and its clinical feasibility and effectiveness were assessed. Results: A total of 14 patients undergoing left upper lobe surgery and left upper mediastinal lymph node dissection were enrolled. The EZB was introduced and positioned without any problems and sufficient lung collapse was achieved in all patients. No tracheobronchial injuries or immediate complications occurred. A stable EMG signal was present in all patients and no RLN palsy and no negative side effects of the NIM EMG ETT or the EZB were observed postoperatively. Conclusions: The described method is technically feasible, easy to apply and save. It provides both reliable IONM and independent lung separation for optimal surgical exposure. The combined use of the EZB and the NIM EMG ETT might reduce the risk for RLN palsy and impaired lung separation during left thoracic surgery with high risk for RLN injury.
CRIS-Team Scopus Importer:2019-07-02
Keywords: EZ-Blocker; Intraoperative monitoring; One-lung ventilation; Recurrent laryngeal nerve; Thoracic surgery

Comparative study of the McGrath™ videolaryngoscope blades and conventional laryngoscopy efficacy during mechanical chest compressions: Insights from a randomized trial with 90 anesthesiologists on objective and subjective parameters - Golditz, Tobias; Schmidt, Joachim; Birkholz, Torsten; Danzl, Anja; Moritz, Andreas; Ackermann, Andreas; Irouschek, Andrea (PLoS ONE, 2024)
Aims This study aimed to compare the efficacy and utility of the McGrath™ videolaryngoscope, using the Macintosh-like McGrath™ MAC blade and the hyperangulated McGrath™ MAC Xblade with a conventional Macintosh blade under simulated resuscitation conditions. Methods A prospective, randomized study under conditions mimicking ongoing chest compressions was conducted with 90 anesthesiologists. Intubation success rates, time-to-vocal cords, time-to-intubate, and time-to-ventilate were measured. Additionally, the study assessed the subjective ratings and the perceived workload using the ‘NASA-task-load-index’ during the procedure. Results The overall intubation success rate was device dependent 99–100%. The McGrath™ MAC and McGrath™ MAC Xblade showed faster visualization times compared to conventional blades. The MAC blade demonstrated superior performance in time-to-intubate and time-to-ventilate compared to both conventional and MAC Xblades. Despite excellent visualization, the MAC Xblade posed challenges in tube placement, reflected in a prolonged intubation time of >120 seconds in one case. Both MAC and MAC Xblade reduced potential dental injuries and interruptions to chest compressions compared to conventional laryngoscopes. User experience significantly impacted intubation times with conventional laryngoscopes, but this effect was mitigated with videolaryngoscopy. Participants reported lower stress and effort when using videolaryngoscopes, with the MAC blade rated superior in perceived time pressure. Conclusion The study supports the superiority of videolaryngoscopy with a Macintosh-like blade over conventional laryngoscopy during mechanical chest compressions, particularly for less experienced users. The McGrath™ MAC blade, in particular, offers advantages in intubation time, user-friendliness, and reduced stress. However, the MAC Xblade’s challenges during tube placement highlight the need for further clinical validation. Continued research is essential to refine guidelines and improve resuscitation outcomes.
CRIS-Team Scopus Importer:2024-09-27

Comparison of clinical outcome variables in patients with and without etomidate-facilitated anesthesia induction ahead of major cardiac surgery: a retrospective analysis - Heinrich, Stefan; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Harig, Frank; Castellanos, Ixchel (Critical Care, 2014)
It is well known that etomidate may cause adrenal insufficiency. However, the clinical relevance of adrenal suppression after a single dose of etomidate remains vague. The aim of this study was to investigate the association between the administration of a single dose of etomidate or an alternative induction regime ahead of major cardiac surgery and clinical outcome parameters associated with adrenal suppression and onset of sepsis.The anesthesia and intensive care unit (ICU) records from patients undergoing cardiac surgery over five consecutive years (2008 to 2012) were retrospectively analyzed. The focus of the analysis was on clinical parameters like mortality, ventilation hours, renal failure, and sepsis-linked serum parameters. Multivariate analysis and Cox regression were applied to derive the results.In total, 3,054 patient records were analyzed. A group of 1,775 (58%) patients received a single dose of etomidate; 1,279 (42%) patients did not receive etomidate at any time. There was no difference in distribution of age, American Society of Anesthesiologists physical score, duration of surgery, and Acute Physiology and Chronic Health Evaluation II score. Postoperative data showed no significant differences between the two groups in regard to mortality (6.8% versus 6.4%), mean of mechanical ventilation hours (21.2 versus 19.7), days in the ICU (2.6 versus 2.5), hospital days (18.7 versus 17.4), sepsis-associated parameters, Sequential Organ Failure Assessment score, and incidence of renal failure. Administration of etomidate showed no significant influence (P = 0.6) on hospital mortality in the multivariate Cox analysis.This study found no evidence for differences in key clinical outcome parameters based on anesthesia induction with or without administration of a single dose of etomidate. In consequence, etomidate might remain an acceptable option for single-dose anesthesia induction.
EVALuna2:16090

Comparison of glidescope core, C-MAC miller and conventional miller laryngoscope for difficult airway management by anesthetists with limited and extensive experience in a simulated Pierre Robin sequence: A randomized crossover manikin study - Moritz, Andreas; Holzhauser, Luise; Fuchte, Tobias; Kremer, Sven; Schmidt, Joachim; Irouschek, Andrea (PLoS ONE, 2021)
Background Video laryngoscopy is an effective tool in the management of difficult pediatric airway. However, evidence to guide the choice of the most appropriate video laryngoscope (VL) for airway management in pediatric patients with Pierre Robin syndrome (PRS) is insufficient. Therefore, the aim of this study was to compare the efficacy of the Glidescope® Core™ with a hyperangulated blade, the C-MAC® with a nonangulated Miller blade (C-MAC® Miller) and a conventional Miller laryngoscope when used by anesthetists with limited and extensive experience in simulated Pierre Robin sequence. Methods Forty-three anesthetists with limited experience and forty-three anesthetists with extensive experience participated in our randomized crossover manikin trial. Each performed endotracheal intubation with the Glidescope® Core™ with a hyperangulated blade, the C-MAC® with a Miller blade and the conventional Miller laryngoscope. “Time to intubate” was the primary endpoint. Secondary endpoints were “time to vocal cords”, “time to ventilate”, overall success rate, number of intubation attempts and optimization maneuvers, Cormack-Lehane score, severity of dental trauma and subjective impressions. Results Both hyperangulated and nonangulated VLs provided superior intubation conditions. The Glidescope® Core™ enabled the best glottic view, caused the least dental trauma and significantly decreased the “time to vocal cords”. However, the failure rate of intubation was 14% with the Glidescope® Core™, 4.7% with the Miller laryngoscope and only 2.3% with the C-MAC® Miller when used by anesthetists with extensive previous experience. In addition, the “time to intubate”, the “time to ventilate” and the number of optimization maneuvers were significantly increased using the Glidescope® Core™. In the hands of anesthetists with limited previous experience, the failure rate was 11.6% with the Glidescope® Core™ and 7% with the Miller laryngoscope. Using the C-MAC® Miller, the overall success rate increased to 100%. No differences in the “time to intubate” or “time to ventilate” were observed. Conclusions The nonangulated C-MAC® Miller facilitated correct placement of the endotracheal tube and showed the highest overall success rate. Our results therefore suggest that the C-MAC® Miller could be beneficial and may contribute to increased safety in the airway management of infants with PRS when used by anesthetists with limited and extensive experience.
CRIS-Team Scopus Importer:2021-05-07

Comparison of Glidescope® Go™, King Vision™, Dahlhausen VL, I‑View™ and Macintosh laryngoscope use during difficult airway management simulation by experienced and inexperienced emergency medical staff: A randomized crossover manikin study - Moritz, Andreas; Leonhardt, Veronika; Prottengeier, Johannes; Birkholz, Torsten; Schmidt, Joachim; Irouschek, Andrea (PLoS ONE, 2020)
BACKGROUND: In pre-hospital emergency care, video laryngoscopes (VLs) with disposable blades are preferably used due to hygienic reasons. However, there is limited existing data on the use of VLs with disposable blades by emergency medical staff. Therefore, the aim of this study was to compare the efficacy of four different VLs with disposable blades and the conventional standard Macintosh laryngoscope, when used by anesthetists with extensive previous experience and paramedics with little previous experience in endotracheal intubation (ETI) in a simulated difficult airway. METHODS: Fifty-eight anesthetists and fifty-four paramedics participated in our randomized crossover manikin trial. Each performed ETI with the new Glidescope® Go™, the Dahlhausen VL, the King Vision™, the I-View™ and the Macintosh laryngoscope. "Time to intubate" was the primary endpoint. Secondary endpoints were "time to vocal cords", "time to ventilate", overall success rate, number of intubation attempts and optimization maneuvers, Cormack-Lehane score, severity of dental compression and subjective impressions. RESULTS: The Glidescope® Go™, the Dahlhausen VL and the King Vision™ provided superior intubation conditions in both groups without affecting the number of intubation attempts or the time required for successful intubation. When used by anesthetists with extensive experience in ETI, the use of VLs did not affect the overall success rate. In the hands of paramedics with little previous experience in ETI, the failure rate with the Macintosh laryngoscope (14.8%) decreased to 3.7% using the Glidescope® Go™ and the Dahlhausen VL. Despite the advantages of hyperangulated video laryngoscopes, the I-View™ performed worst. CONCLUSIONS: VLs with hyperangulated blades facilitated ETI in both groups and decreased the failure rate by an absolute 11.1% when used by paramedics with little previous experience in ETI. Our results therefore suggest that hyperangulated VLs could be beneficial and might be the method of choice in comparable settings, especially for emergency medical staff with less experience in ETI.
CRIS-Team Scopus Importer:2020-08-14

Comparison of Metal and Plastic Disposable Laryngoscope Blade with Reusable Macintosh Blade in Difficult and Inhalation Injury Airway Scenario: A Manikin Study - Moritz, Andreas; Heinrich, Stefan; Irouschek, Andrea; Birkholz, Torsten; Prottengeier, Johannes; Schmidt, Joachim (Journal of Emergency Medicine, 2017)
Single-use plastic blades (SUPB) and single-use metal blades (SUMB) for direct laryngoscopy and tracheal intubation have not yet been compared with reusable metal blades (RUMB) in difficult airway scenarios.The purpose of our manikin study was to compare the effectiveness of these different laryngoscope blades in a difficult airway scenario, as well as in a difficult airway scenario with simulated severe inhalation injury.Thirty anesthetists performed tracheal intubation (TI) with each of the three laryngoscope blades in the two scenario manikins.In the inhalation injury scenario, SUPB were associated with prolonged intubation times when compared with the metal blades. In the inhalation injury scenario, both metal laryngoscope blades provided a quicker, easier, and safer TI. In the difficult airway scenario, intubation times were significantly prolonged in the SUPB group in comparison to the RUMB group, but there were no significant differences between the SUPB and the SUMB. In this scenario, the RUMB demonstrated the shortest intubation times and seems to be the most effective device.Generally, results are in line with previous studies showing significant disadvantages of SUPB in both manikin scenarios. Therefore, metal blades might be beneficial, especially in the airway management of patients with inhalation injury.
EVALuna2:16733

Comparison of Xenon with LED illuminant in difficult and inhalation injury airway scenario: A randomized crossover manikin study - Moritz, Andreas; Prottengeier, Johannes; Schmidt, Joachim (American Journal of Emergency Medicine, 2017)
PURPOSE: The purpose of this study was to compare the effectiveness of a Xenon halogen with a light-emitting diode (LED) laryngoscope light handle in a difficult airway scenario, as well as in an inhalation injury airway scenario that combines a difficult airway and a limited view. METHODS: We recruited forty-two anesthetists into a randomized crossover trial. Each performed tracheal intubation (TI) with a Xenon halogen and a LED light handle in the two manikin scenarios. The primary endpoint was the "time to intubate". Other endpoints were the "time to vocal cords", the "time to ventilate", the rate of successful intubation, the number of intubation attempts, the Cormack-Lehane score, the number of optimization maneuvers, the number of audible dental click sounds indicating dental damage and subjective impressions. RESULTS: In the difficult airway scenario, no significant differences in the recorded intubation times were observed. In the inhalation injury airway scenario, the intubation times were significantly shorter using the LED light handle. Regarding the subjective values, the LED illuminant enabled a significant better view and illumination of the oropharyngeal space and the vocal cords, in both manikin scenarios. CONCLUSION: The LED laryngoscope light handle did not affect the recorded intubation times in the simulated difficult airway scenario, but provided significant advantages in the inhalation injury airway scenario that combines a difficult airway with a limited view caused by a sooted pharynx. We therefore hypothesize, that the LED illuminant might be beneficial in the airway management of burn patients with severe inhalation injury.
EVALuna2:35114

Management of the Expected Difficult Airway with Planned One-Lung Ventilation: A Retrospective Analysis of 44 Cases - Irouschek, Andrea; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Trufa, Denis; Sirbu, Horia; Golditz, Tobias (Thoracic and Cardiovascular Surgeon, 2024)
Background Difficult airway management is essential in anesthesia practice. Particular challenges are posed to patients who require intraoperative one-lung ventilation. Specific guidelines for these scenarios have been lacking. The recent update of German guidelines incorporates recommendations for securing the airway in anticipated difficult airway scenarios in patients requiring one-lung ventilation. However, scientific data on this specific topic is rare. Methods A retrospective analysis was conducted on adult patients undergoing thoracic surgery with one-lung ventilation from 2016 to 2021. During these years, the standard of practice has been in line with the now published guidelines. Patients with anticipated difficult airways were identified, and airway management strategies were analyzed. Results Among 3,197 anesthetic procedures, 44 cases involved anticipated difficult airways, primarily due to prior head and neck tumor treatment. Nasal bronchoscopic awake intubation followed by oral reintubation under videolaryngoscopic inspection and the use of bronchial blockers was the standard procedure. No severe complications were recorded, and one-lung ventilation was maintained successfully in all cases. Discussion The study highlights the challenges of managing difficult airways during thoracic surgery. Recommendations align with recent guidelines, emphasizing the importance of tailored approaches. The use of single-lumen tubes with bronchial blockers appears favorable over double-lumen tubes, offering comparable ventilation quality with reduced risks. Conclusion Despite limitations, the study underscores the safety and efficacy of tailored airway management strategies during one-lung ventilation in patients with anticipated difficult airways. The presented approach offers patient safety and practicability. Further multicenter studies are warranted to validate these findings and refine clinical approaches.
CRIS-Team Scopus Importer:2024-11-29
Keywords: airway (includes related subject matter); anesthesia (includes related subject matter); practice guidelines; thoracoscopy/VATS; ventilation

Nociception testing during fixed-wing ambulance flights. An interventional pilot study on the effects of flight-related environmental changes on the nociception of healthy volunteers - Prottengeier, Johannes; Elsner, Stefan; Wehrfritz, Andreas; Moritz, Andreas; Schmidt, Joachim; Meyer, Michael (PLoS ONE, 2020)
Background: The effects of environmental changes on the somato-sensory system during long-distance air ambulance flights need to be further investigated. Changes in nociceptive capacity are conceivable in light of previous studies performed under related environmental settings. We used standardized somato-sensory testing to investigate nociception in healthy volunteers during air-ambulance flights. Methods: Twenty-five healthy individuals were submitted to a test compilation analogous to the quantitative sensory testing battery-performed during actual air-ambulance flights. Measurements were paired around the major changes of external factors during take-off/climb and descent/ landing. Bland-Altman-Plots were calculated to identify possible systemic effects. Results: Bland-Altman-analyses suggest that the thresholds of stimulus detection and pain as well as above-threshold pain along critical waypoints of travel are not subject to systemic effects but instead demonstrate random variations. Conclusions: We provide a novel description of a real-life experimental setup and demonstrate the general feasibility of performing somato-sensory testing during ambulance flights. No systematic effects on the nociception of healthy individuals were apparent from our data. Our findings open up the possibility of future investigations into potential effects of ambulance flights on patients suffering acute or chronic pain.
CRIS-Team Scopus Importer:2020-03-06

One-lung ventilation after rapid-sequence intubation: a novel approach using an ETView tracheoscopic ventilation tube for placement of an EZ-Blocker without bronchoscopy - Moritz, Andreas; Schreiner, Waldemar; Schmidt, Joachim (Journal of Clinical Anesthesia, 2016)
EVALuna2:16729

Sedation assessment in a mobile intensive care unit: a prospective pilot-study on the relation of clinical sedation scales and the bispectral index - Prottengeier, Johannes; Moritz, Andreas; Heinrich, Stefan; Gall, Christine; Schmidt, Joachim (Critical Care, 2014)
The critically-ill undergoing inter-hospital transfers commonly receive sedatives in continuation of their therapeutic regime or to facilitate a safe transfer shielded from external stressors. While sedation assessment is well established in critical care in general, there is only little data available relating to the special conditions during patient transport and their effect on patient sedation levels. The aim of this prospective study was to investigate the feasibility and relationship of clinical sedation assessment (Richmond Agitation-Sedation Scale (RASS)) and objective physiological monitoring (bispectral index (BIS)) during patient transfers in our Mobile-ICU.The levels of sedation of 30 pharmacologically sedated patients were evaluated at 12 to 17 distinct measurement points spread strategically over the course of a transfer by use of the RASS and BIS. To investigate the relation between the RASS and the BIS, Spearman's squared rank correlation coefficient (?(2)) and the Kendall's rank correlation coefficient (?) were calculated. The diagnostic value of the BIS with respect to the RASS was investigated by its sensitivity and positive predictive value for possible patient awakening. Therefore, measurements were dichotomized considering a clinically sensible threshold of 80 for BIS-values and classifying RASS values being nonnegative.Spearman's rank correlation resulted to ?(2) = 0.431 (confidence interval (CI) = 0.341 to 0.513). The Kendall's correlation coefficient was calculated as ? = 0.522 (CI = 0.459 to 0.576). Awakening of patients (RASS >= 0) was detected by a BIS value of 80 and above with a sensitivity of 0.97 (CI = 0.89 to 1.00) and a positive predictive value of 0.59 (CI = 0.45 to 0.71).Our study demonstrates that the BIS-Monitor can be used for the assessment of sedation levels in the intricate environment of a Mobile-ICU, especially when well-established clinical scores as the RASS are impracticable. The use of BIS is highly sensitive in the detection of unwanted awakening of patients during transfers.
EVALuna2:5483

Single mission workload and influencing factors in German prehospital emergency medicine - A nationwide prospective survey of 1361emergency missions - Prottengeier, Johannes; Keunecke, Johann Georg; Gall, Christine; Eiche, Christian; Moritz, Andreas; Birkholz, Torsten (Scandinavian Journal of Trauma Resuscitation & Emergency Medicine, 2019)
Background: Workload is a major determinant of system performance and human well-being. This study aims to evaluate workload in prehospital emergency medicine on a single mission level and investigates influencing factors originating from medical scenarios, patient-provider interaction, EMS logistics and teamwork. Methods: In a nationwide study, German paramedics were asked to evaluate single missions for perceived workload by completing the NASA Task-Load-Index (TLX). A variety of candidate variables were documented and tested for influence on the TLX through multivariate regression analysis. Results: One thousand three hundred sixty-one emergency missions were analysed. Global workload scored in medium ranges (Median TLX 41.00/100; IQR 24.25-57.50). 263 missions achieved very low (< 20/100) and 52 missions achieved very high (> 80/100) levels of workload. Severity of distress as indicated by the NACA score (delta TLX 2.71 per 1 NACA point), execution of invasive procedures (e.g. delta TLX 8.20 for intravenous access), obese patients (delta TLX 0.05 per 1 kg of weight) and aggression incidences (e.g. delta TLX 10.54 for physical aggression), amongst others, resulted in significant increases in workload. Good teamwork decreased workload by 2.18 points per 1 point on the Weller-Teamwork Measurement Tool. Conclusion: Distinct factors result in significant increases in workload for EMS paramedics. Improvements in training for certain medical scenarios, strategies against aggression events and enhancements in EMS logistics - especially for the transfer of obese patients - should be implemented and tested for their presumably positive effect on workload, EMS performance and paramedics' well-being.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Emergency medical service; Ergonomics; Human factors; NASA task-load-index; Paramedic; Teamwork; Workload

The effect of a standardised source of divided attention in airway management: A randomised, crossover, interventional manikin study - Prottengeier, Johannes; Petzoldt, Marlen; Jess, Nikola; Moritz, Andreas; Gall, Christine; Schmidt, Joachim; Breuer, Georg (European Journal of Anaesthesiology, 2016)
Dual-tasking, the need to divide attention between concurrent tasks, causes a severe increase in workload in emergency situations and yet there is no standardised training simulation scenario for this key difficulty.We introduced and validated a quantifiable source of divided attention and investigated its effects on performance and workload in airway management.A randomised, crossover, interventional simulation study.Center for Training and Simulation, Department of Anaesthesiology, Erlangen University Hospital, Germany.One hundred and fifty volunteer medical students, paramedics and anaesthesiologists of all levels of training.Participants secured the airway of a manikin using a supraglottic airway, conventional endotracheal intubation and video-assisted endotracheal intubation with and without the Paced Auditory Serial Addition Test (PASAT), which served as a quantifiable source of divided attention.Primary endpoint was the time for the completion of each airway task. Secondary endpoints were the number of procedural mistakes made and the perceived workload as measured by the National Aeronautics and Space Administration's task load index (NASA-TLX). This is a six-dimensional questionnaire, which assesses the perception of demands, performance and frustration with respect to a task on a scale of 0 to 100.All 150 participants completed the tests. Volunteers perceived our test to be challenging (99%) and the experience of stress and distraction true to an emergency situation (80%), but still fair (98%) and entertaining (95%). The negative effects of divided attention were reproducible in participants of all levels of expertise. Time consumption and perceived workload increased and almost half the participants make procedural mistakes under divided attention. The supraglottic airway technique was least affected by divided attention.The scenario was effective for simulation training involving divided attention in acute care medicine. The significant effects on performance and perceived workload demonstrate the validity of the model, which was also characterised by high acceptability, technical simplicity and a novel degree of standardisation.
EVALuna2:5546

The epidemiology of airplane headache: A cross-sectional study on point prevalence and characteristics in 50,000 travelers - Konrad, Fabian; Moritz, Andreas; Moritz, Michael; Keunecke, Johann Georg; Tischler, Felix; Prottengeier, Johannes (Cephalalgia, 2022)
Background The current knowledge on the epidemiology and clinical manifestation of airplane headache is mostly derived from case series and small cohort studies without evidence from large populations. Methods This cross-sectional study was conducted over a five-month period in the arrival area of two international airports in Germany. 50,000 disembarking passengers were addressed about headaches during their flight to determine headache prevalence, and those confirming and willing to participate underwent a structured interview. Results Headache during travel was reported by 374 passengers (0.75%), and 301 underwent a structured interview. One hundred and one (0.2%) met the diagnostic criteria of airplane headache. Six passengers suffered from migraines and 134 from tension-type headaches. The differences in the age and gender distribution between the airplane headache and non-airplane headache groups were not statistically significant. The onset (79.2%), duration (82.2%), and location (73.3%) of airplane headache mostly complied with current diagnostic criteria but pain intensity (42.6%) and quality (42.6%) did less so. Conclusion Our data suggest a substantially lower prevalence of airplane headaches than previously reported. The pain intensity and quality seem less characteristic than assumed, suggesting a need to refine the current diagnostic criteria.
CRIS-Team WoS Importer:2022-04-29
Keywords: Airplane headache; barotrauma; cross-sectional data; headache disorders; primary; headache attributed to airplane travel; headache attributed to disorders of homeostasis; International Classification of Headache Disorders; secondary headache disorders

The EZ-blocker for one-lung ventilation in patients undergoing thoracic surgery: clinical applications and experience in 100 cases in a routine clinical setting - Moritz, Andreas; Irouschek, Andrea; Birkholz, Torsten; Prottengeier, Johannes; Sirbu, Horia; Schmidt, Joachim (Journal of Cardiothoracic Surgery, 2018)
BACKGROUND: In certain clinical situations the insertion of a double-lumen tube (DLT) for one-lung ventilation (OLV) is not feasible or unfavorable. In these cases, the EZ-Blocker (EZB) may serve as an alternative. The aim of our analysis was to report on the clinical applications and our experience with the EZB for one-lung ventilation in 100 patients undergoing thoracic surgery. METHODS: All anesthetic records from patients older than 18 years of age undergoing general anesthesia in the department of thoracic surgery with intraoperative use of an EZB for OLV at the University Hospital of Erlangen in four consecutive years were analyzed retrospectively. RESULTS: Most frequently, EZB was used in difficult airway (27%) and for surgical procedures with high risk for left recurrent laryngeal nerve injury (21%), followed by application in intubated (12%) or tracheostomized (11%) patients. 11% of the patients had an increased risk of gastric regurgitation. Almost all EZBs were placed free of complications (99%). Clinically sufficient lung collapse was achieved in all patients. No serious airway injuries or immediate complications were documented. CONCLUSIONS: The EZB is an efficient, easy-to-use and safe airway device and enables OLV in several clinical situations, when conventional DLTs are not feasible or less favorable. Three major applications were depicted from the data: expected difficult airway, surgical procedures with necessity of intraoperative recurrent laryngeal nerve monitoring and already intubated or tracheostomized patients.
EVALuna2:35112

Video double-lumen tube for one lung ventilation: implementation and experience in 343 cases of routine clinical use during the first 20 months of the SARS-CoV-2 pandemic - Irouschek, Andrea; Schmidt, Joachim; Birkholz, Torsten; Sirbu, Horia; Moritz, Andreas (Journal of Cardiothoracic Surgery, 2024)
Background: Double-lumen tubes (DLTs) are the preferred device for lung isolation. Conventional DLTs (cDLT) need a bronchoscopic position control. Visualisation of correct DLT positioning could be facilitated by the use of a video double-lumen tube (vDLT). During the SARS-CoV-2-pandemic, avoiding aerosol-generation was suggesting using this device. In a large retrospective series, we report both general and pandemic related experiences with the device. Methods: All anesthesia records from patients aged 18 years or older undergoing surgery from April 1st, 2020 to December 31st, 2021 in the department of thoracic surgery requiring intraoperative lung isolation were analyzed retrospectively. Results: During the investigation period 343 left-sided vDLTs (77.4%) and 100 left-sided cDLTs (22.6%) were used for one lung ventilation. In the vDLT group bronchoscopy could be reduced by 85.4% related to the cDLT group. Additional bronchoscopy to reach or maintain correct position was needed in 11% of the cases. Other bronchoscopy indications occured in 3.6% of the cases. With cDLT, in 1% bronchoscopy for other indications than conforming position was observed. Conclusions: The Ambu® VivaSight™ vDLT is an efficient, easy-to-use and safe airway device for the generation of one lung ventilation in patients undergoing thoracic surgery. The vDLT implementation was achieved easily with full interchangeability to the left-sided cDLT. Using the vDLT can reduce the need for aerosol-generating bronchoscopic interventions by 85.4%. Continuous video view to the carina enabling position monitoring of the DLT without need for bronchoscopy might be beneficial for both employee’s and patient’s safety.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Double-lumen tube; One lung ventilation; SARS-CoV-2; Thoracic surgery; Video double-lumen tube